(untitled) (International Journal of Innovative Computing, 2024)
Advancements in digital technology have considerably boosted productivity and economic growth over time. Numerous businesses and organizations use a variety of software to organize their work efficiently. This system’s main objective is to convert from a manual to an automated method for more effective management. An Employee Management System is one of the systems that contribute significantly to the management of a business. However, this article highlights the deployment of an automated system to replace the paper-based approach that general contractor companies have been using for decades. Laravel is one of the most popular framework technologies for system development among developers. Laravel enables developers to concentrate on the design architecture and functionality of an online application, making it easier for other developers to manage their tasks. Furthermore, role-based access control (RBAC) in Contractor Management System (CMS) has increased the system’s security by granting users access depending on their jobs. On-site users will be able to access the system with the tip of their fingers. This development aims to simplify the organization’s staff management and will elaborate further on the technologies employed in the proposed system.